Revisiting economic distance and its role in foreign subsidiary survival - Arte, Pratik; Larimo, Jorma (Inderscience Publishers, 2023)
In this study, we argue the coexistence of arbitrage and costs associated with economic distance engender a non-linear relationship between foreign subsidiary survival and economic distance. Specifically, we suggest that low to medium economically distant countries offer scope of economic arbitrage, whereas the cost of operating in medium to high economically distant countries is substantially high. We construct an index of economic distance using arguments from the eclectic paradigm of international production and organisational learning theory and base our measurement on the Mahalanobis method of distance calculation. Empirical analysis is conducted by applying the Cox's proportional hazard model to a sample of 1771 Finnish foreign direct investments. Results suggest that subsidiary survival has an inverted U-shaped relationship with economic distance. Firms with host country experience and wholly owned subsidiaries are able to mitigate the costs of operating in economically distant countries, while joint ventures are better suited for economically similar countries.
Keywords: economic distance; establishment mode; ownership advantages; ownership mode; subsidiary survival; fi=Kansainvälinen liiketoiminta|en=International Business|